The PTEN/PI3K/AKT Pathway in vivo, Cancer Mouse Models - Carnero, Amancio; Paramio, Jesus M. (Frontiers in Oncology, 2014)
When PI3K (phosphatidylinositol-3 kinase) is activated by receptor tyrosine kinases, it phosphorylates PIP2 to generate PIP3 and activates the signaling pathway. Phosphatase and tensin homolog deleted on chromosome 10 dephosphorylates PIP3 to PIP2, and thus, negatively regulates the pathway. AKT (v-akt murine thymoma viral oncogene homolog; protein kinase B) is activated downstream of PIP3 and mediates physiological processes. Furthermore, substantial crosstalk exists with other signaling networks at all levels of the PI3K pathway. Because of its diverse array, gene mutations, and amplifications and also as a consequence of its central role in several signal transduction pathways, the PI3K-dependent axis is frequently activated in many tumors and is an attractive therapeutic target. The preclinical testing and analysis of these novel therapies requires appropriate and well-tailored systems. Mouse models in which this pathway has been genetically modified have been essential in understanding the role that this pathway plays in the tumorigenesis process. Here, we review cancer mouse models in which the PI3K/AKT pathway has been genetically modified.